2015
DOI: 10.1007/s13318-015-0254-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the pharmacokinetics of three different preparations of total flavones of Hippophae rhamnoides in beagle dogs after oral administration

Abstract: Pharmacokinetic properties of isorhamnetin, quercetin, and kaempferol in three different total flavones of Hippophae rhamnoides (TFH) preparations were compared after oral administration to beagle dogs by a UPLC-MS method. The pharmacokinetic results showed that C max of isorhamnetin and quercetin in TFH solid dispersion (TFH-SD) and TFH self-emulsifying (TFH-SE) preparations was significantly enhanced than that in TFH preparations (p < 0.05). The AUCs of isorhamnetin and quercetin in TFH-SD were 5.9- and 3.1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Compared with Duan (Duan and others ) and Xie's (Xie and others ) work on solid dispersion formulations (composed of Poloxamer 188 and ethanol), our study contained less surfactants but performed a comparable bioavailability improvement, all of which could increase the bioavailability of quercetin around 3.0‐fold of those in suspension. Although similar components (MCT, CrEL, and Trans HP at ratios of 13.26: 60.38: 26.36) were used to form self‐microemulsions as a comparison to Duan and Zhao's development (SE composed of MCT CrEL, and 1,2‐propanediol at ratios of 5:57:38; Zhao and others ; Duan and others ), quite different enhancement levels were existed. When taken the TFH suspension as the same control group, our approach could improve the bioavailability of quercetin about 2‐fold of this reported SE formulation.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Compared with Duan (Duan and others ) and Xie's (Xie and others ) work on solid dispersion formulations (composed of Poloxamer 188 and ethanol), our study contained less surfactants but performed a comparable bioavailability improvement, all of which could increase the bioavailability of quercetin around 3.0‐fold of those in suspension. Although similar components (MCT, CrEL, and Trans HP at ratios of 13.26: 60.38: 26.36) were used to form self‐microemulsions as a comparison to Duan and Zhao's development (SE composed of MCT CrEL, and 1,2‐propanediol at ratios of 5:57:38; Zhao and others ; Duan and others ), quite different enhancement levels were existed. When taken the TFH suspension as the same control group, our approach could improve the bioavailability of quercetin about 2‐fold of this reported SE formulation.…”
Section: Resultsmentioning
confidence: 83%
“…When take the same compound, quercetin as the representative of TFH, literatures have reported several approaches to improve the bioavailability of TFH. The relevant bioavailability of quercetin was enhanced 3.1 times and 2.4 times when encapsulated in solid dispersions (SD) and self‐emulsions (SE), respectively after oral administration in beagle dogs (Duan and others ), and in the case of oral administration in rats, this bioavailability of quercetin was boosted to 3.16 (in SD form) and 1.55 (in SE form) times, separately (Zhao and others ). Compared with Duan (Duan and others ) and Xie's (Xie and others ) work on solid dispersion formulations (composed of Poloxamer 188 and ethanol), our study contained less surfactants but performed a comparable bioavailability improvement, all of which could increase the bioavailability of quercetin around 3.0‐fold of those in suspension.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, quercetin reached the Tmax at 5.58 hr, 4.50 hr, 4.25 hr, and kaempferol reached the Tmax at 7.08 hr, 6.00 hr, 7.00 hr at low, middle and high doses, respectively (Li et al, 2012). In beagle dogs, Tmax of isorhamnetin and quercetin were 2.6 hr and 1.0 hr (Duan et al, 2016). These studies indicated that both passive diffusion and active transport involved in absorption forms of FSBT, and passive diffusion process was dominated.…”
Section: Absorptionmentioning
confidence: 98%